Polar bear sightings during MOSAiC Expedition PS122 - Verena Mohaupt; Bjela König (PANGAEA, 2025)
Polar bear sightings and encounters during the MOSAiC expedition (PS122.1 - PS122.5) Observations taken by the Logistic Team, stating date and coordinates, number of animals, condition and activity of animals and actions taken by the expedition team. Bear guards with flare and rifles have been present on the ice at all times when people were on the ice as well as a person on watch on the bridge and stern of the vessel. Standard procedure for any bear observations in the proximity of RV Polarstern/site when people were on the ice was always the immediate evacuation of the floe or site. CO stands for extquotesingleCentral Observatory extquotesingle next to RV Polarstern.